Deutsch im Vergleich. Sprachliche Strukturen im Kontrast zum Italienischen: Einführung in das Themenheft - Katelhön, Peggy; Brambilla, Marina; Muco, Albana (Linguistik Online, 2021)
This thematic issue of Linguistik online is dedicated to Contrastive linguistics for the language pair Italian-German. The contributions collected here deal with Italian-German language comparison from different points of view. The common feature of all of them is a corpus-oriented approach. Using authentic attestations from different linguistic sources, the linguistic structures of both languages are analysed and compared with each other. The granular and fine-grained comparison enabled the authors to work out interesting results not only in the fields of morphology and syntax, but also for pragmatics, and text and discourse linguistics for both languages, which can be profitably used in foreign language didactics, theoretical linguistics and translation studies.